Characteristics That May Help in the Identification of Potentially Confusing Proprietary Drug Names. (March 2017) - Shah, Millie B.; Merchant, Lubna; Chan, Irene Z.; Taylor, Kellie
Purpose: This study aimed to provide a descriptive analysis of characteristics that are common among drug name pairs involved in name confusion medication errors. Methods: We evaluated drug name pairs that contained at least one proprietary name from the Institute for Safe Medication Practices (ISMP) List of Confused Drug Names. For each name pair, we analyzed whether the following characteristics were present: (1) the same first letter, (2) a shared letter string of at least 3 letters, and (3) similarity in the number of letters. Additionally, we obtained the combined Phonetic and Orthographic Computer Analysis (POCA) score. Results: Ninety-nine percent of the drug name pairs reflected at least one of the 3 characteristics analyzed. Additionally, 75% of the names had a combined POCA score of ≥50%. Conclusions: This descriptive analysis provides some insight into characteristics that may be associated with name confusion, which should be considered when formulating and evaluating proposed proprietary drug names.